Adult thymic medullary epithelium is maintained and regenerated by linage-restricted cells rather than bipotent progenitors - Ohigashi, I; Zuklys, S; Sakata, M; Mayer, C; Hamazaki, Y; Minato, N; Hollander, G; Takahama, Y (Cell Press, 2015)
Medullary thymic epithelial cells (mTECs) play an essential role in establishing self-tolerance in T cells. mTECs originate from bipotent TEC progenitors that generate both mTECs and cortical TECs (cTECs), although mTEC-restricted progenitors also have been reported. Here, we report in vivo fate-mapping analysis of cells that transcribe β5t, a cTEC trait expressed in bipotent progenitors, during a given period in mice. We show that, in adult mice, most mTECs are derived from progenitors that transcribe β5t during embryogenesis and the neonatal period up to 1 week of age. The contribution of adult β5t+ progenitors was minor even during injury-triggered regeneration. Our results further demonstrate that adult mTEC-restricted progenitors are derived from perinatal β5t+ progenitors. These results indicate that the adult thymic medullary epithelium is maintained and regenerated by mTEC-lineage cells that pass beyond the bipotent stage during early ontogeny.